Characteristics of Barotropic Energy Conversion in Rapid Intensifying and Decaying Tropical Cyclones Over the Western North Pacific. Issue 4 (15th February 2023) - Cao, Xi; Wu, Renguang; Zhu, Peijun; Lan, Xiaoqing; Dai, Yifeng; Bi, Mingyu; Wen, Guanhuan; Wang, Yuanhao
Abstract: The prediction of the tropical cyclone (TC) intensity remains a difficult issue. This study analyzes local instantaneous barotropic kinetic energy conversion in the lower troposphere in rapid intensifying (RI) and rapid decaying (RD) TCs over the western North Pacific (WNP) during June through November from 1979 to 2017. The kinetic energy conversion to the synoptic eddies is separated for climatological mean, interannual and intraseasonal flows. It is found that the intraseasonal cyclonic flows display a northwest‐southeast orientation in the RI TCs, but a circular feature in the RD TCs. Intraseasonal and climatological mean zonal flows contribute together to the positive kinetic energy conversion in the northwest quadrant of the RI TCs. Intraseasonal meridional flows induce positive (negative) kinetic energy conversion in the northeast (south) part of the RD TCs. The kinetic energy conversion associated with interannual flows is small for both the RI and RD TCs. Plain Language Summary: The damage caused by the tropical cyclones (TCs) is closely related to their intensity. Revealing the factors of the intensification of the TCs may help to improve the skill of prediction of the TC intensity and reduce the damage of the TCs. From the energetic point of view, the intensification of the TCs requires the conversion of energy from the background flows. Here, we compare the barotropic kinetic energy conversion in the rapid intensifying (RI) and decaying (RD) TCs over the western North Pacific during June through November. Our analysis reveals that the intraseasonal flows have the largest contribution to both the RI and decaying TCs through the kinetic energy conversion to the synoptic scale eddies. The climatological mean flows have a secondary contribution to the RI TCs. The contribution of the interannual flows to the kinetic energy conversion is small for both the RI and RD TCs. Our results signify the importance of the configuration and magnitude of the background flows relative to the synoptic scale disturbances in the barotropic kinetic energy conversion for the TC intensity changes. Key Points: Intraseasonal cyclonic flows feature a northwest‐southeast and circular distribution for rapid intensifying (RI) and decaying (RD) tropical cyclones (TCs), respectively Barotropic energy from intraseasonal and mean zonal flows contributes to the RI TCs Barotropic energy conversion from intraseasonal flows are opposite in northeast and south parts of the RD TCs